Pengaruh Variasi Komposisi BCTMP (Bleached Chemi Thermo Mechanical Pulp) dan LBKP (Leaf Bleached Kraft Pulp) Terhadap Karakteristik Kertas Mengunakan Metode Handsheet - Widia Zulfa Ariani; Nurlela Nurlela; Agus Wahyudi (Jurnal Inovasi Teknik Kimia, 2026)
Indonesia has great potential to provide raw materials that support the sustainability of the pulp and paper industry. Global paper consumption continues to increase every year. That is, around 394 million tons per year. To maintain its competitiveness, paper industry producers continue to innovate to reduce production costs without ignoring paper quality. One strategy implemented is to eliminate the use of long fiber (NBKP), which is more expensive, and to replace some of the short-fiber chemical pulp (LBKP) with other, more economical raw materials, such as BCTMP (Bleached Chemi Thermo Mechanical Pulp). Therefore, the author conducted a study on the Effect of Variations in BCTMP and LBKP Composition on paper characteristics. The method used in this study is the handsheet method. This study aims to determine the effects of BCTMP and LBKP composition on paper characteristics and to identify the optimal BCTMP + LBKP composition. Based on the results of the study, it can be concluded that the higher the BCTMP composition in the pulp mixture, the higher the Thickness, bulk, and opacity values ​​produced. Conversely, the higher the BCTMP composition in the pulp mixture, the lower the Tensile strength and Brightness values ​​produced. Furthermore, the composition of 90% LBKP + 10% BCTMP yields the best results compared to the others. This formulation is recommended for use in paper production to improve paper quality